Preparation of Glass Fiber/Poly(Ether Ether Ketone) Composite Foam with Improved Compressive Strength and Heat Resistance. Issue 3 (13th January 2022) - Liang, Liubo; Jiang, Botao; Wu, Tonghua; Ma, Youmei; Zhang, Shuling; Wang, Guibin
Abstract : Glass fiber/poly(ether ether ketone) (GF/PEEK) composite foams with improved compressive strength and heat resistance can be successfully prepared using a simple and environmentally friendly supercritical carbon dioxide (sc‐CO2 ) foaming technology. The cell morphologies of the foams can be controlled by adjusting the GF content and foaming parameters, including the saturation temperature, saturation time, saturation pressure, and depressurization rate. With a foam density of 0.55 g cm −3, the PEEK‐based composite foam having 30% GF content has a 10% compressive strength of 11.07 MPa, and its density varies negligibly up to 330.0 °C. The GF/PEEK composite foams having high GF contents show significantly better properties than those having low GF contents as a result of the supporting and strengthening effect of the GF in the PEEK cell walls. The GF/PEEK composite foams also show good corrosion resistance. As a result of these properties, the GF/PEEK composite foams are promising high‐performance materials for use in extreme environments. Abstract : Using supercritical carbon dioxide as the blowing agent, glass fiber (GF)/poly(ether ether ketone) (PEEK) composite foams can be prepared by the near‐melting‐point saturation rapid depressurization method. The addition of glass fiber strengthens the cell walls in the foam, resulting in the excellent compressive strength, heat resistance, and corrosion resistance.